Impact of Senior Government Policies on the Renewal of Built Capital for Rural Non-Profits. Issue 5 (19th October 2020) - Ryser, Laura; Halseth, Greg; Markey, Sean
ABSTRACT: Changes in rural service provision have been shaped by a shift from state to private and nonprofit service delivery, driven by a neo-liberal policy orientation. As senior governments continue to offload the delivery of services to nonprofit stakeholders in rural regions, state policies often fail to address deficiencies with aging and inappropriate built capital assets. The infrastructure and service deficit undermines the capacity of the nonprofit sector, and threatens the overall resilience of rural communities. At the community level, nonprofits have been pursuing new institutional/structural arrangements and exploring opportunities to address infrastructure deficiencies in order to strengthen their resilience within neo-liberal public policy approaches. Building upon 51 key informant interviews in 35 small communities in British Columbia, Canada, our research addresses gaps in understanding how senior government policies are developing conditions necessary to support the renewal of infrastructure assets in the nonprofit sector. Our findings suggest that senior government policy and funding structures may not provide the conditions necessary to enable nonprofits to renew their built capital assets that could strengthen the long-term viability of rural service provision. These findings reinforce the need for post COVID-19, or similar recession response stimulus, initiatives to include wise infrastructure investments that enhance the capacity and efficiency of rural nonprofit service providers.